Processing method for improving performance of aluminum alloy based on accumulative ply rolling
Through the processing method based on accumulation stacking and rolling, combined with solid solution treatment and aging treatment, the problem of reduced elongation when preparing ultrafine crystal aluminum alloys is solved, which significantly improves the strength and plasticity of the aluminum alloy and achieves higher comprehensive performance.
Patent Information
- Application Number
- CN202510117949.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
AI Technical Summary
When the prior art prepares ultrafine crystalline aluminum alloys through large plastic deformation, the elongation rate is reduced, making it difficult to meet industrial needs. At the same time, the plate shape is inaccurate, interface influence, and cumbersome surface cleaning during the rolling process.
Using a processing method based on accumulation stacking, high-density dislocation ultrafine crystalline materials are prepared through solid solution treatment, surface pretreatment, rolling and aging treatment, and the comprehensive performance of the materials is further improved through subsequent solid solution-aging treatment.
Through this method, the ultrafine crystalline material with up to 7 passes was successfully prepared, with significantly improved strength and improved plasticity. The overall performance was better than that of the original sheet, meeting industrial needs.
Smart Images

Figure CN119870153A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloy processing, and in particular to a processing method for improving aluminum alloy performance based on cumulative rolling. Background Art
[0002] In recent years, as people pay more and more attention to energy and environmental issues, and the increase in the number of cars has led to a continuous increase in energy demand, the impact of exhaust emissions on environmental pollution during energy consumption cannot be ignored. As an important development direction of the automobile industry, automobile lightweighting plays an important role in energy conservation and emission reduction. Among them, the use of lightweight materials to replace the original steel as much as possible to reduce the overall weight of the car body is one of the most representative studies in the development of automobile lightweighting in recent years. Automobile lightweighting means reducing the overall weight of the car body and reducing energy consumption while ensuring the safety performance of the car, so as to better achieve the purpose of energy conservation and emission reduction. Among them, aluminum alloy is the most representative of lightweight materials. A large number of studies have shown that the amount of aluminum used in the automotive industry is increasing year by year. Aluminum alloy has the characteristics of low density, high specific strength and good corrosion resistance. It is widely used in aerospace, transportation and chemical industries, but its strength cannot meet the requirements of some key components. Therefore, a processing technology is urgently needed to further improve the performance of aluminum alloy. As an emerging plastic deformation method, large plastic deformation (SPD) introduces a large amount of strain during the deformation process, thereby effectively refining the grains and improving the performance of the material. However, during the processing, due to the introduction of a large number of dislocations, the strength of the material increases and the plasticity decreases, that is, the phenomenon of work hardening occurs, which cannot meet industrial needs and is prone to brittle fracture. Although during the deformation process, the grains are continuously broken and refined, resulting in fine grain strengthening and a slight increase in plasticity, this is far from making up for the loss of plasticity caused by work hardening. Therefore, a series of subsequent heat treatment processes are needed to improve the comprehensive performance of the material.
[0003] The aging process is one of the main strengthening methods for heat-treatable aluminum alloys. During the aging process, the precipitated second phase can effectively hinder the movement of dislocations, thereby improving the strength of the material. The present invention prepares an ultrafine-grained aluminum alloy by cumulative rolling bond (ARB). During the deformation process, the elongation is bound to drop sharply due to the influence of work hardening. Subsequently, artificial aging treatment (AA) and solution-aging (T6 treatment) and other heat treatment processes are combined to improve the overall comprehensive performance of the material, providing a new way to further improve the performance of aluminum alloys and expand the application of aluminum alloys.
[0004] Among them, Chinese patent CN201911398036.9 proposes a composite large plastic deformation method for preparing ultrafine-grained aluminum and aluminum alloys, and ultrafine-grained aluminum alloys are prepared by equal channel extrusion and multi-directional forging. First, the sample is subjected to 4 equal channel extrusions, during which the extrusion direction is perpendicular to the previous pass, and then multi-directional forging is performed 2 times, a total of 6 times, to obtain ultrafine-grained materials. According to statistics, after the fourth equal channel angular extrusion is completed, the proportion of large grains (≥1μm) is still high, and the grain size is extremely uneven. After multi-directional forging, the grains become further fine, and the large grains are refined. After the sixth multi-directional compression is completed, the grains become fine and uniform and close to equiaxed, and an ultrafine-grained material with uniform organization and good anisotropy is obtained, which effectively improves work efficiency, reduces costs, and is conducive to large-scale production.
[0005] In addition, Chinese patent CN202311114186.9 discloses a heat treatment process for metal alloys after large plastic deformation. First, a fine-grained structure with high-density dislocations is obtained through a corrugated molding process. At this time, the material is in a high-energy unstable state after deformation, and it is very easy to undergo static recrystallization at high temperature. The premature occurrence of recrystallization will also cause the grains to grow and coarsen prematurely. Therefore, energy removal treatment is required before subsequent heat treatment, that is, keeping at 150°C for 12h, then keeping at 400°C for 2h for solution treatment, and then keeping at 135°C for 16h for aging treatment. The results show that the sample without energy removal treatment has obvious grain coarsening in a short time (15min) of solid solution, and the second phase particles are coarser in the subsequent aging process. The sample treated with energy removal has better fine grain components after solid solution and aging treatment, and the second phase precipitation is more dispersed and fine, and the performance is more excellent.
[0006] Both of the above patents prepare ultrafine-grained structures through large plastic deformation. It can be seen that the research on preparing fine-grained materials through large plastic deformation process has gradually matured, but the research on further improving the comprehensive performance of deformed materials through subsequent heat treatment is relatively rare.
[0007] Based on the above, it can be seen that the existing technology has the following limitations or shortcomings:
[0008] 1. The elongation of the specimens prepared by large plastic deformation is reduced and often cannot meet industrial needs.
[0009] 2. During the rolling process, the plate shape of the sample cannot be accurately grasped, and cracks may form on the edge, causing difficulties for the next pass.
[0010] 3. Accumulative rolling is a process in which two or more plates are repeatedly stacked and rolled to form the desired material. The interface formed between the plates will have an adverse effect on the final performance of the material.
[0011] 4. The sample surface cleaning process is rather complicated and the current production efficiency is low.
[0012] Based on this, the present invention aims to further improve the overall comprehensive performance of high-density dislocation ultrafine-grained materials formed by large plastic deformation through a heat treatment process, thereby improving the performance of commercial aluminum alloys. Summary of the invention
[0013] In view of this, the purpose of the present invention is to propose a processing method for improving the performance of aluminum alloy based on cumulative rolling which is reliable and has good processing effect.
[0014] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0015] A processing method for improving the performance of aluminum alloy based on cumulative rolling, comprising:
[0016] S01, take two aluminum alloy plates of preset specifications, whose length is along the rolling direction;
[0017] S02, respectively performing solid solution treatment on the two aluminum alloy plates to obtain two solid solution products;
[0018] S03, performing surface pretreatment on two solid solution products;
[0019] S04, stacking two solid solution products and fixing both ends;
[0020] S05. At room temperature, rolling the two stacked solid solution products to obtain rolled products, wherein during the rolling process, the reduction amount each time is 50%±5% of the total thickness of the two solid solution products, and the rolling speed is 0.18±0.02 m / s;
[0021] S06. Cut the rolled product after S05 processing in half, and then repeat S03 to S05 until a rolled product with a cumulative rolling number reaching a preset number of passes is obtained, which is recorded as a rolled sample (ARB), and the processing is completed to obtain an aluminum alloy product.
[0022] As a possible implementation manner, further, in this solution S01, the aluminum alloy plate is an AA6061-T6 aluminum alloy plate.
[0023] As a possible implementation mode, further, in the present solution S02, the temperature of the solution treatment is 500±10°C, and the treatment time is 1 hour.
[0024] As a possible implementation mode, further, in the present solution S03, the surface pretreatment method is to clean and degrease the surface of the solid solution product with acetone, and then remove the oxide layer attached to the surface of the solid solution product.
[0025] As a possible implementation mode, further, in the present solution S05, the amount of reduction each time is 50% of the total thickness of the two solid solution products, and the rolling speed is 0.18 m / s.
[0026] As a possible implementation mode, further, in the present solution S06, after the cumulative number of rolling passes reaches 7, the processing is completed to obtain the aluminum alloy product.
[0027] As a preferred post-processing implementation option, preferably, in the present scheme S06, after obtaining the rolled product, an aging treatment is also performed on it, and the aging treatment temperature is 170° C. and the duration is 6-10 hours.
[0028] As another preferred post-processing implementation option, preferably, in this scheme S06, after obtaining the rolled product, it is also subjected to solution treatment and aging treatment in sequence; wherein the temperature of the solution treatment is 530°C, and the solution holding time is 30 minutes; the temperature of the aging treatment is 170°C, and the time is 14-18 hours.
[0029] Based on the above, the present invention also proposes an aluminum alloy product, which is produced by the processing method described above.
[0030] By adopting the above technical scheme, the present invention has the following beneficial effects compared with the prior art: This scheme successfully prepares ultrafine-grained materials with up to 7 passes through the process of cumulative rolling in large plastic deformation. As the number of passes increases, the strength of the sample continues to increase, but the plasticity continues to decrease. Although the plasticity rises slowly in higher passes due to the effect of fine grain strengthening, it cannot meet industrial needs. In order to better improve the comprehensive performance of rolled products, the present invention further develops two different heat treatment methods, aging and solution-aging. After heat treatment, the strength and plasticity of the obtained product are improved, and its overall performance is better than that of the original plate. The present invention provides a new idea for improving the performance of AA6061 aluminum alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a brief workflow and test item diagram of the processing method of the embodiment of this solution;
[0033] Figure 2 This is a simplified schematic diagram of the appearance of a sample when the sample is tested in the embodiment of the present invention;
[0034] Figure 3 This is one of the comparison graphs of the hardness change curve and stress-strain curve of the test sample in the embodiment of this scheme;
[0035] Figure 4 This is a comparison chart of the results of the aging peaks of the aging treatment and the solution aging treatment in the embodiment of the present scheme;
[0036] Figure 5 This is the second comparison chart of the stress-strain curves of the test samples in the embodiment of this scheme;
[0037] Figure 6 This is the third comparison chart of the stress-strain curves of the test samples in the embodiment of this scheme;
[0038] Figure 7 It is a comparison chart of the results of testing the mechanical properties of the samples in the embodiment of this scheme. DETAILED DESCRIPTION
[0039] The present invention will be further described in detail below in conjunction with the accompanying drawings and examples. It is particularly noted that the following examples are only used to illustrate the present invention, but are not intended to limit the scope of the present invention. Similarly, the following examples are only partial embodiments of the present invention rather than all embodiments, and all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention.
[0040] Combination Figure 1 As shown, this embodiment provides a processing method for improving the performance of aluminum alloy based on cumulative rolling, which includes:
[0041] S01, take two aluminum alloy plates of preset specifications, whose length is along the rolling direction;
[0042] S02, respectively performing solid solution treatment on the two aluminum alloy plates to obtain two solid solution products;
[0043] S03, performing surface pretreatment on two solid solution products;
[0044] S04, stacking two solid solution products and fixing both ends;
[0045] S05. At room temperature, rolling the two stacked solid solution products to obtain rolled products, wherein during the rolling process, the reduction amount each time is 50%±5% of the total thickness of the two solid solution products, and the rolling speed is 0.18±0.02 m / s;
[0046] S06, cutting the rolled product after S05 processing in half, and then repeating S03 to S05 until the rolled product with the cumulative rolling times reaching the preset times is obtained, completing the processing and obtaining the aluminum alloy product.
[0047] Among them, in this scheme S01, the aluminum alloy plate is an AA6061-T6 aluminum alloy plate.
[0048] Furthermore, in the present scheme S02, the temperature of the solution treatment is 500±10°C and the treatment time is 1 hour.
[0049] In terms of surface pretreatment, as a possible implementation method, further, in this scheme S03, the surface pretreatment method is to clean and degrease the surface of the solid solution product with acetone, and then remove the oxide layer attached to the surface of the solid solution product.
[0050] In the present scheme S05, the amount of reduction each time is 50% of the total thickness of the two solid solution products, and the rolling speed is 0.18 m / s.
[0051] As a possible implementation mode, further, in the present solution S06, after the cumulative number of rolling passes reaches 7, the processing is completed to obtain the aluminum alloy product.
[0052] As a preferred post-processing implementation option, preferably, in the present scheme S06, after obtaining the rolled product, an aging treatment is also performed on it, and the aging treatment temperature is 170° C. and the duration is 6-10 hours.
[0053] As another preferred post-processing implementation option, preferably, in this scheme S06, after obtaining the rolled product, it is also subjected to solution treatment and aging treatment in sequence; wherein the temperature of the solution treatment is 530°C, and the solution holding time is 30 minutes; the temperature of the aging treatment is 170°C, and the time is 14-18 hours.
[0054] In order to further elaborate on this solution, an example is provided below to illustrate its implementation, which includes the following:
[0055] A processing method for improving the performance of aluminum alloy based on cumulative rolling, comprising:
[0056] (1) Two specimens with a size of 150 mm x 75 mm x 2 mm were selected from commercial AA6061-T6 aluminum alloy plates (denoted as T6), with the length along the rolling direction;
[0057] (2) In order to improve the work hardening degree of the sample during rolling, the two T6 samples in step (1) were first subjected to solution treatment (temperature of 500 °C, time of 1 h) to dissolve the second phase particles back and obtain a supersaturated solid solution, thus preparing a solid solution state sample (denoted as ST);
[0058] (3) In order to ensure the close adhesion of the interface between the two plates during rolling, the surface of the ST sample was first degreased with acetone, and then the oxide layer on the rolling surface was removed with a wire brush to increase friction;
[0059] (4) The samples were stacked with a total thickness of 4 mm, and the two ends of the plates (ST samples with degreased and oxide layer removed) were fixed with steel wire to prevent displacement during rolling;
[0060] (5) Perform room temperature rolling treatment, with each rolling reduction amount being 50% of the total thickness of the sample and a rolling speed of 0.18 m / s. After the first rolling pass is completed, the sample is cut in half and steps (3) to (5) are repeated. The total cumulative number of passes is 7, which are recorded as the rolled sample (ARB) to obtain an aluminum alloy product.
[0061] In order to facilitate the evaluation of the effect of the number of rolling passes on the performance of the obtained aluminum alloy products, the present embodiment also prepared aluminum alloy products with 1, 3, and 5 rolling passes respectively and compared the tensile properties with the rolled samples with 7 rolling passes (respectively denoted as ARB-1, ARB-3, ARB-5, and ARB-7); at the same time, the commercial AA6061-T6 aluminum alloy plate (T6) of step (1) and the solid solution state sample (ST) prepared in step (2) were used as controls.
[0062] The specifications of the samples are as follows: Figure 2 As shown, the material used in the experiment of this embodiment is a 6061-T6 aluminum alloy plate with a thickness of 2 mm. During the sample preparation process, tensile samples were selected along the rolling direction (RD). To reduce the error, 3 tensile samples were selected for each sample. The tensile strength and elongation were taken as the average of the 3 tensile samples as the final data. Subsequently, tensile tests were carried out on T6, ST, ARBx (x = 1, 3, 5, 7) samples at room temperature to obtain the changes in tensile strength and elongation of each sample under different conditions.
[0063] Combination Figure 3As shown in the figure, after the tensile test, by making the hardness change curves and stress-strain curves of T6, ST, and ARBx samples, it can be learned that with the progress of rolling, the hardness and hardness of the ARB sample increase significantly, showing an obvious work hardening phenomenon. The strength increases significantly with the increase in the number of passes, while the elongation decreases significantly. The ARB3 sample has the lowest elongation, which is only 4.7%, which is far from meeting industrial needs. The ARB7 sample has the highest strength, which is 405.3MPa, and the elongation at break increases more gently, which may be provided by fine grain strengthening.
[0064] In order to further explore the changes in the performance of rolled samples after post-processing, this plan also proposes the following two post-processing methods, both of which involve aging treatment, and the peak aging of the aging treatment is determined by testing the hardness of the sample.
[0065] In terms of hardness testing, this program uses MR3000 microhardness tester to perform Vickers hardness test (HV) on the RD-ND surfaces of the specimens. To reduce the error, 10 points are selected for each sample, the maximum and minimum values are removed, and the average value is taken as the final data of the hardness test. The test force is 200g and the loading time is 15s.
[0066] As a better post-processing implementation option, preferably, in this scheme S06, after obtaining the rolled product, it is also subjected to aging treatment, and the aging treatment temperature is 170° C. and the duration is 0-16 hours.
[0067] As another preferred post-processing implementation option, preferably, in this scheme S06, after obtaining the rolled product, it is also subjected to solution treatment and aging treatment in sequence; wherein the temperature of the solution treatment is 530°C, and the solution holding time is 30 minutes; the temperature of the aging treatment is 170°C, and the time is 0-20 hours.
[0068] Among them, Figure 4 As shown, the aging peak time of the above two post-processing schemes is compared in combination with the hardness test results; it can be seen that in the post-processing scheme with only aging treatment, the aging peak time is 8h, and in the post-processing scheme with solid solution + aging treatment, the aging peak time is 16h.
[0069] Based on the above, the two post-processing methods mentioned in this embodiment specifically include:
[0070] (1) In S06, after the rolled product is obtained, it is subjected to aging treatment at a temperature of 170°C and a duration of 8 hours.
[0071] For the convenience of comparison, a solid solution sample (ST) was also taken for isoparametric aging treatment, and the sample was recorded as ST-170℃-PA;
[0072] After the equal parameter aging treatment, the corresponding samples with different rolling times were recorded as ARB1-170℃-PA, ARB3-170℃-PA, ARB5-170℃-PA, and ARB7-170℃-PA.
[0073] Combination Figure 5 As shown in the figure, after the tensile test, the engineering stress-strain curves of ST-170℃-PA, ARB1-170℃-PA, ARB3-170℃-PA, ARB5-170℃-PA and ARB7-170℃-PA samples were drawn. It can be seen that after aging treatment, the comprehensive performance of the solid solution samples and the rolled samples are significantly improved, and their strength and elongation are improved to a certain extent compared with the rolled samples ARBx (x=1, 3, 5, 7) without aging treatment. This is mainly because the low-temperature aging treatment causes the dislocations to rearrange or even annihilate, reduces the degree of work hardening, and improves the elongation. The improvement in strength is due to the precipitation of the second phase particles, which increases the overall strength of the sample.
[0074] (2) In S06, after the rolled product is obtained, it is subjected to solution treatment and aging treatment in sequence; the temperature of the solution treatment is 530°C, and the solution holding time is 30 minutes; the temperature of the aging treatment is 170°C, and the time is 16 hours.
[0075] For the convenience of comparison, the initial T6 aluminum alloy plate was also taken for solid solution and aging treatment with equal parameters, and the sample was recorded as T6-FST30-170PA;
[0076] The corresponding samples with different rolling times were recorded as ARB1-FST30-170PA, ARB3-FST30-170PA, ARB5-FST30-170PA, and ARB7-FST30-170PA after equal parameter solid solution and aging treatment.
[0077] Combination Figure 6 As shown in the figure, after the tensile test, the engineering stress-strain curves of T6-FST30-170PA, ARB1-FST30-170PA, ARB3-FST30-170PA, ARB5-FST30-170PA and ARB7-FST30-170PA samples were drawn. It can be seen that after solution-aging treatment, the strength of ARB1-FST30-170PA, ARB3-FST30-170PA, ARB5-FST30-170PA and ARB7-FST30-170PA samples decreased slightly, but the elongation was significantly improved, and their performance was significantly better than that of the original T6 state samples at higher passes.
[0078] Combining the above experiments, Figure 7As shown, the mechanical properties of ST, ARB, ARB-170PA and ARB-FST30-170PA samples are compared, where the horizontal axis is the number of rolling times, and the sample with 0 rolling times is the solid solution state sample ST.
[0079] It can be seen that although the strength of the ARB sample obtained through the aforementioned processing method steps (1) to (5) increases with the increase in the number of passes, the plasticity decreases sharply and is far from meeting the industrial demand. On the basis of rolling, the strength and elongation of the ARB-170PA sample after aging treatment are further improved on the basis of the performance of the sample only rolled, and its comprehensive performance is improved to a certain extent. The elongation of the ARB-FST30-170PA sample after solution-aging treatment is further improved on the basis of the sample after aging treatment, but the strength decreases slightly.
[0080] In summary, through cumulative rolling and subsequent two different heat treatment processes, this scheme found that the comprehensive performance of the samples after aging was well improved, that is, the strength and elongation were improved to a certain extent. The strength of the samples after solution-aging treatment decreased slightly, but the elongation was further improved. This shows that it is feasible to improve the comprehensive performance of the ARB samples after rolling through cumulative rolling and further heat treatment processes in this scheme.
[0081] The above descriptions are only some embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Any equivalent device or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A processing method for improving the performance of aluminum alloy based on cumulative rolling, characterized in that: It includes: S01, take two aluminum alloy plates of preset specifications, whose length is along the rolling direction; S02, respectively performing solid solution treatment on the two aluminum alloy plates to obtain two solid solution products; S03, performing surface pretreatment on two solid solution products; S04, stacking two solid solution products and fixing both ends; S05. At room temperature, rolling the two stacked solid solution products to obtain rolled products, wherein during the rolling process, the reduction amount each time is 50%±5% of the total thickness of the two solid solution products, and the rolling speed is 0.18±0.02 m / s; S06, cutting the rolled product after S05 processing in half, and then repeating S03 to S05 until the rolled product with the cumulative rolling times reaching the preset times is obtained, completing the processing and obtaining the aluminum alloy product.
2. The processing method for improving the performance of aluminum alloy based on cumulative rolling as claimed in claim 1, characterized in that: In S01, the aluminum alloy plate is an AA6061-T6 aluminum alloy plate.
3. The processing method for improving the performance of aluminum alloy based on cumulative rolling as claimed in claim 1, characterized in that: In S02, the temperature of the solution treatment is 500±10°C and the treatment time is 1h.
4. The processing method for improving the performance of aluminum alloy based on cumulative rolling as claimed in claim 1, characterized in that: In S03, the surface pretreatment method is to clean and degrease the surface of the solid solution product with acetone, and then remove the oxide layer attached to the surface of the solid solution product.
5. The processing method for improving the performance of aluminum alloy based on cumulative rolling as claimed in claim 1, characterized in that: In S05, the reduction amount each time is 50% of the total thickness of the two solid solution products, and the rolling speed is 0.18 m / s.
6. The processing method for improving the performance of aluminum alloy based on cumulative rolling as claimed in claim 1, characterized in that: In S06, after the cumulative rolling times reaches 5 to 7 passes, the processing is completed to obtain the aluminum alloy product.
7. The processing method for improving the performance of aluminum alloy based on cumulative rolling according to any one of claims 1 to 6, characterized in that: In S06, after the rolled product is obtained, it is subjected to aging treatment at a temperature of 170° C. for 6-10 hours.
8. The processing method for improving the performance of aluminum alloy based on cumulative rolling according to any one of claims 1 to 6, characterized in that: In S06, after the rolled product is obtained, it is subjected to solution treatment and aging treatment in sequence; Among them, the temperature of solution treatment is 530℃, and the solution holding time is 30min; The aging treatment temperature is 170°C and the duration is 14-18 hours.
9. An aluminum alloy product, characterized in that: It is obtained by the processing method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Composite large plastic deformation method for preparing ultrafine grain aluminum and aluminum alloys
CN111097806A
Heat treatment process for metal alloy subjected to severe plastic deformation
CN117089783A
Grain refinement method of 7000 series aluminum alloy
CN103572179A
Preparation method of heterogeneous layered aluminum-based composite material
CN111376572A
Method for preparing gradient structure metal material through incremental-cumulative ply rolling
CN112845587A
Cited By
Preparation method of heterogeneous aluminum alloy composite board
CN121423372A